Peningkatan kemampuan menulis cerita dengan menggunakan metode picture and picture pada siswa kelas IV SDN 02 Kalirejo - Fiqih Athaini (Action Research Journal, 2021)
This study aims to improve the students' story writing skills and increase the activeness in writing stories for the fourth grade students of SDN 02 Kalirejo through the application of the picture and picture method. This research is a Classroom Action Research (CAR). This research was carried out in two cycles, each cycle consisting of planning, implementing actions, observing, and reflecting. The research subjects were the fourth grade students of SDN 02 Kalirejo Pekalongan, totaling 18 students. The results showed that using the picture and picture method could increase the students' activeness and ability to write stories from pre-cycle to cycle I and from cycle I to cycle II. The results showed that: 1) learning by using the picture and picture method on the subject of writing stories can increase student activity. This can be seen from the results of observations of the student learning process, namely, before the action of 45%, the second cycle of 65% and the second cycle of 80%. 2) Learning using the picture and picture method can improve students' story writing skills. The improvement of students' mastery learning outcomes in writing stories can be seen from the results of students' work, namely, before the action of 44.44%, the first cycle of 66.67%, and in the second cycle of 88.89%.